XML-based mobile agents - Steele, R.; Dillon, Tharam S.; Pandya, P.; Ventsov, Y. (IEEE, 2005)
Current mobile agent systems are based on agent architectures that are partially or fully implementation programming language-specific. Mobile agent implementation in a specific programming language has usage limitations as the inter agent communication and agent migration to other agent hosts needs support for the same language. Widely used Java-based agents have an advantage of easy agent migration through bytecode transfer but this also imposes the requirement of a Java virtual machine (JVM) on each agent host where agents can migrate. To achieve a truly system independent and agent system architecture independent solution, we propose a XML-based mobile agent architecture. This paper presents a mobile agent system design based on the use of XML-based agent code, the UDDI registry for agent registration and lookup/discovery and XML Web service calls for mobile agent intercommunication and migration. This also facilitates industry to have easier and less risky adaptation from existing agent system implementation.